INTERVIEW: JANE McGONIGAL. (Smithsonian, 2011)
An interview with computer-game developer Jane McGonigal is presented. She discusses the use of games for educational purposes and for problem solving, noting a social entrepreneurship game she developed with the World Bank Institute called Evoke. When asked about the social health of gaming, she cites the ability of games to improve interpersonal relationships. McGonigal also discusses her online social network for gamers called "Gameful."